A Complete Set of Shadow Prices for Pakistan: Illustrations for 1975-76 (The Pakistan Development Review, 1988)
A consistent set of economy-wide shadow prices for Pakistan is presented, based on input-output flows for the mid-1970s. This provides broad parameters for policy at the sel10ral level, with indications as to which sectors should be encouraged under alternative assumptions concerning the behaviour of factor markets. Further, these parameters arc useful as inputs for project evaluation. A number of agricultural and manufacturing sectors arc identified as being socially profitable. Finally, the shadow prices will be taken as parameters in a tax reform exercise.